Learning Management of Students with Special Needs in Schools: Manajemen Pembelajaran Peserta Didik Berkebutuhan Khusus di Sekolah - Isnaini Maulida Rahmawati; Adi Bandono (Academia Open, 2022)
This research is qualitative research with research subjects including principals, coordinators/responsible for inclusion, special assistant teachers, classroom teachers, GDPK guardians. The research setting is at the Creative School of SD Muhammadiyah 2 Tulangan Sidoarjo. Data collection techniques used are interviews, observation, and documentation. Meanwhile, the data analysis and data interpretation techniques according to Miles and Hubermen are data reduction, data presentation, and conclusion drawing and data verification. The results of this study indicate that: (1) The GDPK learning planning at the Creative School of SD Muhammadiyah 2 Tulangan Sidoarjo has been carried out carefully, starting from needs analysis, recruitment, orientation or FORTASI, mapping or placement of PDBK, prota, prosem, syllabus, RPP, PPI , to the determination of learning media or special educational teaching aids, (2) The organization that has been carried out has been running as expected under the leadership of the Principal who collaborates with relevant stakeholders, in order to achieve effective, efficient and productive criteria, (3) The implementation of GDPK learning has been running quite good and effective by implementing modifications to curriculum content that are tailored to the needs of PDBK, PPI, link books, green books, therapy, and special programs, (4) Monitoring and evaluation of GDPK learning has been running quite well and effectively carried out by the supervisor of the local education office , principals, curriculum coordinators, and h . delivery the results of the development of PDBK to the guardians of students, (5) the obstacles and efforts that have been made in implementing the learning management of PDBK in the Creative School of SD Muhamamadiyah 2 reinforcement Sidoarjo, namely the lack of provision of special assistant teachers, not yet 100% of the fulfillment of media or special educational teaching aids, the existence of the dual role of the classroom teacher before the special assistant teacher.